e-PG Pathshala: A survey on student's experience & its perspective in North-Central Universities of India - Sana Aslam; Sharad Kumar Sonkar; Abhishek Kumar (Social Sciences and Humanities Open)
The main goal of each country is to provide excellent, curriculum-based interactive content for every subject and make it publicly available on a platform for the use of colleges, universities, and other educational establishments worldwide. Web-based learning systems significantly impact global education by giving students access to learning materials at any time, location, and on any device. The Indian government has launched various e-content development projects. One such effort is e-PG Pathshala, a portal to online courses. In this study, we focus on the students' experience and perspective towards e-PG Pathshala in the north-central universities of India, which has 362 students. We chose eight north-central universities in India for library and information science students and took 70 % from each university. The online survey method was employed for data collection, and the acquired data were analyzed using MS Excel and SPSS software, and the mean and standard deviation for descriptive analyses. Chi-square tests were used to evaluate the validity of the results. The results indicated that most of the respondents (70.68 %) were postgraduate, and the maximum number of respondents (36.12 %) accessed e-PG Pathshala to prepare for semester exams. The majority of the students (28.11 %) have the perception that the content of e-PG Pathshala is freely available.